A Rare Cause of Elbow Pain, Osteoid Osteoma of the Coronoid Process of the Ulna: Report of a Case - Barati, Hasan; Mirbolouk , Ahmadreza; Baroutkoub, Mojtaba; Moqaddam, Masoud; Tavakolidarestani, Reza (Journal of Clinical Physiotherapy Research, 2022)
Osteoid osteoma is a relatively common benign neoplasm of the bone. An intra-articular osteoid osteoma is a rare form of the tumor with subtle radiologic and clinical findings mimicking an inflammatory arthritis which usually leads to a delayed diagnosis. We reported a 22-year-old male patient with subacute pain and decreased range of motion in his right elbow. Paraclinical evaluations showed a cystic bony lesion of the coronoid process of the proximal ulna that went through the surgical excision. Histopathologic examination revealed an intra-articular osteoid osteoma. The patient had a favorable outcome.